2022
DOI: 10.1021/acs.joc.2c01962
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Chromans from ortho-Quinone Methides and Arylallenes

Abstract: ortho-Quinone methides (o-QMs) underwent formal [4 + 2]-cycloaddition reactions with arylallenes regioselectively at the styrenyl olefin to furnish the corresponding 3-methylene-2-arylchromans in moderate to good yields (up to 88%). When R ≠ H, the reactions also proceeded with moderate stereoselectivity (up to 5:1) which was governed by the nature of the R group. The 3-methylene-2-arylchromans could serve as common intermediates for further functionalization including epoxidation, oxidative cleavage/Baeyer–Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…With ample quantities of both indanone 6 and ( E )- 20c in hand, we were ready to explore the key intermolecular o -QM type [4 + 2]-cycloaddition. Although such reaction is a powerful tool for biosynthesis chromans, its applications to the total synthesis of natural products remain rather scarce. , It was quite discouraging to our investigation that assembly of the F-ring of rubriflordilactone A ( 3 ) via an endo - o -QM type [4 + 2]-cycloaddition by Ploypradith carried an incorrect configuration . Since it has been reported that the endo-/exo-selectivity in the intermolecular Diels–Alder reaction can be modulated by adding an appropriate catalyst to the system or attaching a suitable substituent in the substrate, we envisioned that construction of the F-ring with desired stereocontrol should be achievable via an o -QM type [4 + 2]-cycloaddition approach.…”
mentioning
confidence: 99%
“…With ample quantities of both indanone 6 and ( E )- 20c in hand, we were ready to explore the key intermolecular o -QM type [4 + 2]-cycloaddition. Although such reaction is a powerful tool for biosynthesis chromans, its applications to the total synthesis of natural products remain rather scarce. , It was quite discouraging to our investigation that assembly of the F-ring of rubriflordilactone A ( 3 ) via an endo - o -QM type [4 + 2]-cycloaddition by Ploypradith carried an incorrect configuration . Since it has been reported that the endo-/exo-selectivity in the intermolecular Diels–Alder reaction can be modulated by adding an appropriate catalyst to the system or attaching a suitable substituent in the substrate, we envisioned that construction of the F-ring with desired stereocontrol should be achievable via an o -QM type [4 + 2]-cycloaddition approach.…”
mentioning
confidence: 99%